A method for evaluating the chemical resistance of glass fiber reinforced plastic pressure vessel lining materials
By using a cylindrical sample with a single-head in a fiberglass pressure vessel for chemical media immersion experiments, the penetration and diffusion process of the media in the container to the lining material is simulated, and the performance of chemical media resistance is evaluated using the circumferential tensile strength, the problem of inaccurate evaluation in the prior art is solved and more accurate performance evaluation is achieved.
Patent Information
- Application Number
- CN202211493921.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-25
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2042-11-25
AI Technical Summary
The prior art cannot fully simulate the penetration and diffusion process of chemical media on the lining material in actual applications of fiberglass pressure vessels, resulting in inaccurate evaluation of chemical resistance media performance.
A single-sided immersion experiment of chemical media was performed using a cylindrical sample with a single-capsule head. Through the steps of making steel molds, preparing samples, adding samples to the sample medium, sampling and measurement, the penetration and diffusion process of the media in the container to the lining material, and the annular tensile strength was selected as an index for mechanical properties evaluation.
This method can more accurately evaluate the chemical media resistance of fiberglass pressure vessel lining materials, provide a more reliable material selection basis, and ensure the safe use of the container.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of fiber reinforced thermosetting plastic performance evaluation, and in particular relates to a method for evaluating the chemical medium resistance performance of a fiberglass reinforced plastic pressure vessel lining material. Background Art
[0002] FRP pressure vessels, namely glass fiber reinforced plastic pressure vessels (internal pressure ≤ 0.6MPa), are generally made of thermosetting resins (such as epoxy resins, unsaturated polyester resins, vinyl ester resins, etc.) as matrix materials, and glass fiber and its products (glass fiber chopped strand mats, glass fiber seam mats, glass fiber roving cloth, etc.) as reinforcement materials. Due to the advantages of FRP pressure vessels such as corrosion resistance, light weight, no scaling, easy molding, convenient transportation and installation, they have been gradually promoted and applied in the petroleum, chemical, metallurgy, food, water treatment and other industries in recent years.
[0003] The cylinder of FRP pressure vessels is generally composed of an inner lining layer, a reinforcement layer and an outer protective layer. The inner lining layer is made of chopped strand mat, seam edge mat and glass cloth impregnated with resin, laid layer by layer and cured, and is mainly used to seal the internal medium. The reinforcement layer is made of glass fiber impregnated with resin, wound and cured, and is mainly used to withstand internal pressure loads. The outer protective layer is a gel coat resin with ultraviolet absorbers added, which is mainly used to prevent the container from light aging.
[0004] Since the inner lining of the FRP pressure vessel plays the role of medium sealing, the evaluation of the chemical resistance of the lining material is a key link in the container design process. If the chemical resistance of the lining material is insufficient, the penetration and diffusion of the medium into the material will cause the material performance to deteriorate, the inner lining will leak or even crack, and seriously affect the safe use of the container. At present, most of the evaluation methods for the chemical resistance of the lining material are to use the same material to make a flat specimen, then immerse it in the chemical medium, and regularly measure the appearance, quality, thickness, and bending strength retention rate of the specimen. For materials with multiple surfaces in contact with the medium and with a planar structure in actual applications, the flat specimen is immersed and the bending strength retention rate is measured. This evaluation method can completely simulate the penetration and diffusion process of the medium on the specimen, and is accurate for the chemical resistance evaluation of the planar structure material. However, for the FRP pressure vessel, its cylinder is a ring-shaped curved structure, and the medium only contacts one surface of the inner lining. The method of immersing flat specimens cannot fully simulate the penetration and diffusion process of the medium into the lining material of the FRP pressure vessel, and the measurement of bending strength does not match the actual stress condition of the container cylinder. Therefore, the evaluation of the chemical medium resistance performance of the lining layer is not accurate, and there are often certain deviations in actual experiments.
[0005] It can be seen that in the prior art, it is impossible to fully simulate the penetration and diffusion process of chemical media into the lining material of the container in actual application, and thus it is impossible to accurately evaluate the impact of chemical media on the performance changes of the lining material. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a method for evaluating the chemical medium resistance of the lining material of a glass fiber reinforced plastic pressure vessel. The method can completely simulate the penetration and diffusion process of the chemical medium on the lining material in actual application of the container, so as to accurately evaluate the influence of the chemical medium on the performance change of the lining material, thereby providing a reliable basis for the material selection of the container lining layer and effectively ensuring the safety of the container in later use.
[0007] In order to achieve the above purpose, the present invention adopts the following technical solution:
[0008] A method for evaluating the chemical medium resistance of a glass fiber reinforced plastic pressure vessel lining material, comprising:
[0009] S1: manufacturing a steel mold, wherein the steel mold is composed of a cylinder and a single head;
[0010] S2: A layer of mold release film is attached to the inner surface of the steel mold, and the fiberglass pressure vessel lining material is layered on the inner surface of the steel mold according to the actual layering order and solidified into a shape. After demolding, the mold release film is removed to obtain a sample;
[0011] S3: Add chemical medium into the sample, seal the opening with a sealing film, fix the sample, and start the experiment at the preset temperature;
[0012] S4: At preset intervals, take out the cylindrical specimen with a single head, observe the appearance of the specimen, measure the mass, wall thickness and Barcol hardness of the specimen and record the parameter data, cut multiple annular specimens at the contact point between the specimen and the chemical medium, measure the hoop tensile strength of the annular specimens and take the average value, and calculate the hoop tensile strength retention rate based on the parameter data and the average value of the hoop tensile strength;
[0013] S5: Evaluate the chemical resistance of the FRP pressure vessel lining material. If the hoop tensile strength retention rate is higher, the chemical resistance of the FRP pressure vessel lining material is better; otherwise, the chemical resistance of the FRP pressure vessel lining material is worse.
[0014] Further, in S1, the outer diameter of the cylinder is 100-300 mm, the thickness is 1-6 mm, and the length is 150-300 mm;
[0015] The sealing head is elliptical, and its thickness is the same as that of the cylinder. A through hole with a diameter of 5-15 mm is opened at the center of the sealing head.
[0016] Furthermore, in S3, the sample is placed vertically, and the height of the chemical medium added therein is not less than 150 mm.
[0017] Furthermore, it is characterized in that in S1, after the steel mold is manufactured, its surface and joints are polished.
[0018] Furthermore, it is characterized in that in S2, the release film is a polyethylene film.
[0019] Furthermore, in S2, the ply thickness is 2-5 mm.
[0020] Furthermore, in S2, the lining material of the FRP pressure vessel is composed of impregnated glass fiber surface felt, chopped strand felt and glass cloth; and the sample is cylindrical with a single head.
[0021] Furthermore, in S3, the sealing film is a polytetrafluoroethylene film.
[0022] Furthermore, in S3, a chemical medium is added into the sample, the opening is sealed with a sealing film, a small hole is opened on the surface of the sealing film, the sample is placed vertically in a glass container and fixed securely, and then the experiment is started at a preset temperature.
[0023] Furthermore, in S4, five annular samples with a width of 10-20 mm are cut at the contact point between the sample and the chemical medium.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The present invention provides a method for evaluating the chemical medium resistance of a lining material of a glass fiber reinforced plastic pressure vessel. The method implements the evaluation of the chemical medium resistance of the lining material of the glass fiber reinforced plastic pressure vessel through the steps of making a steel mold, preparing a sample, adding a medium to the sample, sampling and measuring, and evaluating the performance. The method uses a cylindrical sample with a single head to perform a single-sided immersion experiment of a chemical medium, which can better simulate the penetration and diffusion of the chemical medium to the lining material in the glass fiber reinforced plastic pressure vessel. The hoop tensile strength (hoop tensile strength retention rate) is selected as an indicator for mechanical performance evaluation, which can be closer to the actual stress condition of the container. Therefore, the evaluation method provided by the present invention can make a more accurate evaluation of the chemical medium resistance of the lining material of the glass fiber reinforced plastic pressure vessel. The method is simple, practical, easy to operate, and the evaluation result is more accurate. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 A flow chart of a method for evaluating the chemical medium resistance of a glass fiber reinforced plastic pressure vessel lining material provided by the present invention;
[0027] Figure 2This is a graph showing the variation of the circumferential tensile strength measured by a method for evaluating the chemical medium resistance of a glass fiber reinforced plastic pressure vessel lining material in Example 1 of the present invention;
[0028] Figure 3 This is a graph showing the variation in circumferential tensile strength measured by a method for evaluating the chemical medium resistance of a glass fiber reinforced plastic pressure vessel lining material in Example 2 of the present invention. DETAILED DESCRIPTION
[0029] like Figure 1 As shown, the present invention provides a method for evaluating the chemical medium resistance performance of a glass fiber reinforced plastic pressure vessel lining material, comprising:
[0030] S1: Make a steel mold, which consists of a cylinder and a single head; the outer diameter of the cylinder is 100-300mm, the thickness is 1-6mm, and the length is 150-300mm; the head is elliptical, and its thickness is the same as that of the cylinder, and a through hole with a diameter of 5-15mm is opened at the center of the head; after the steel mold is made, grind its surface and joints to ensure a smooth surface.
[0031] S2: A layer of demoulding film (polyethylene film) is attached to the inner surface of the steel mold, and the lining material of the FRP pressure vessel (composed of impregnated glass fiber surface felt, chopped strand felt and glass cloth) is laid on the inner surface of the steel mold according to the actual laying order (the laying thickness is 2-5 mm) and cured to form. After demoulding, the demoulding film (polyethylene film) is removed to obtain a cylindrical specimen with a single head;
[0032] S3: Add chemical medium into the sample, seal the opening with a sealing film (polytetrafluoroethylene film), make a small hole (puncture a small hole) on the surface of the sealing film, make the hole to ensure the balance of internal and external pressures, place the sample vertically in a glass container and fix it firmly, and start the experiment at the preset temperature. Here, place the sample vertically, and the height of the chemical medium added to it is not less than 150mm.
[0033] S4: Take out the cylindrical specimen with a single head at preset intervals, observe the appearance of the specimen, measure the mass, wall thickness and Barcol hardness of the specimen and record the parameter data, cut 5 annular specimens with a width of 10-20 mm at the contact point between the specimen and the chemical medium, measure the hoop tensile strength of the annular specimens and take the average value, and calculate the hoop tensile strength retention rate based on the parameter data and the average value of the hoop tensile strength;
[0034] S5: Evaluate the chemical resistance of the FRP pressure vessel lining material. If the hoop tensile strength retention rate is higher, the chemical resistance of the FRP pressure vessel lining material is better; otherwise, the chemical resistance of the FRP pressure vessel lining material is worse.
[0035] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.
[0036] Example 1
[0037] 1. Weld the steel annular cylinder and a single elliptical head to make a steel mold. The outer diameter of the steel mold cylinder is 150mm, the thickness of the cylinder is 3mm, the length of the cylinder is 200mm, and the thickness of the elliptical head is 3mm. After welding, a hole is opened in the center of the head for demoulding. The hole diameter is 7mm. Then use sandpaper to grind the internal and external welds and surfaces of the steel hollow mold to ensure a smooth surface.
[0038] 2. Taking the composite material of vinyl ester resin and glass fiber products as an example, a layer of polyethylene film is wrapped on the surface of the steel mold for subsequent demoulding, and then the impregnated glass fiber surface felt, chopped strand mat, and glass cloth are laid on the steel mold according to the actual laying order of the lining layer of the glass fiber reinforced plastic pressure vessel. After the laying is completed, it is cured and formed, and the thickness of the layer is 4mm. After the curing is completed, the demoulding is removed and the polyethylene film is removed to obtain the sample. A total of 5 samples are made.
[0039] 3. Pour the chemical medium to be tested into the sample. The chemical medium is a saturated sodium chloride aqueous solution. The medium height is not less than 150mm to ensure full contact with the material. The opening is sealed with a polytetrafluoroethylene film. A small hole is pierced on the surface of the film with a needle to ensure the balance of internal and external pressures. Place it vertically in a glass container and fix it firmly. Soak it at 60°C for 28 days for testing.
[0040] 4. Take out one sample every 7 days and measure the appearance, mass, wall thickness and Barcol hardness of the sample. After the measurement, cut 5 ring samples with a width of 15 mm from the part of the sample in contact with the medium, measure the hoop tensile strength of the ring samples and take the average value. Plot the measured mass, wall thickness, Barcol hardness and hoop tensile strength retention rate against the immersion time.
[0041] 5. By comparing the above experimental data, if the appearance, quality, wall thickness and Barcol hardness of the sample change less, the lining material with a higher hoop tensile strength retention rate has better chemical resistance, otherwise, its chemical resistance is worse.
[0042] The variation of hoop tensile strength with immersion time, such as Figure 1 As shown in the figure, the smaller the changes in the appearance, quality, wall thickness and Barcol hardness of the sample, and the higher the retention rate of the hoop tensile strength of the lining material, the better its chemical resistance performance.
[0043] Example 2
[0044] 1. Weld the steel annular cylinder and a single elliptical head to make a steel mold. The outer diameter of the cylinder of the steel mold is 250mm, the thickness of the cylinder is 5mm, the length of the cylinder is 250mm, and the thickness of the elliptical head is 5mm. After welding, a hole is opened at the center of the head for demoulding. The hole diameter is 10mm. Then use sandpaper to grind the internal and external welds and surfaces of the steel hollow mold to ensure a smooth surface.
[0045] 2. Taking the composite material of vinyl ester resin and glass fiber products as an example, a layer of polyethylene film is wrapped on the surface of the steel mold for subsequent demoulding, and then the impregnated glass fiber surface mat, chopped strand mat, and glass cloth are laid on the steel mold according to the actual laying order of the lining layer of the glass fiber reinforced plastic pressure vessel. After the laying is completed, it is cured and formed, and the thickness of the layer is 3mm. After the curing is completed, the demoulding is removed and the polyethylene film is removed to obtain the sample. A total of 9 samples are made.
[0046] 3. Pour the chemical medium to be tested into the sample. The chemical medium is a saturated calcium chloride aqueous solution. The medium height is not less than 150mm to ensure full contact with the material. The opening is sealed with a polytetrafluoroethylene film. A small hole is pierced on the surface of the film with a needle to ensure the balance of internal and external pressures. Place it vertically in a glass container and fix it firmly. Soak it at 80℃ for 56 days for testing.
[0047] 4. Take out one sample every 7 days and measure the appearance, mass, wall thickness and Barcol hardness of the sample. After the measurement, cut 9 ring samples with a width of 20 mm from the part of the sample in contact with the medium, measure the hoop tensile strength of the ring samples and take the average value. Plot the measured mass, wall thickness, Barcol hardness and hoop tensile strength retention rate against the immersion time.
[0048] 5. By comparing the above experimental data, if the appearance, quality, wall thickness and Barcol hardness of the sample change less, the lining material with a higher hoop tensile strength retention rate has better chemical resistance, otherwise, its chemical resistance is worse.
[0049] The variation of hoop tensile strength with immersion time, such as Figure 2 As shown in the figure, the smaller the changes in the appearance, quality, wall thickness and Barcol hardness of the sample, and the higher the retention rate of the hoop tensile strength of the lining material, the better its chemical resistance performance.
[0050] Although the embodiments of the present invention are described above in conjunction with the accompanying drawings and embodiments, the present invention is not limited to the above-mentioned specific embodiments and application fields, and the above-mentioned specific embodiments are only illustrative and instructive, rather than restrictive. Under the guidance of the specification, those skilled in the art can also make many forms without departing from the scope of protection of the claims of the present invention, all of which belong to the scope of protection of the present invention.
Claims
1. A method for evaluating the chemical resistance of glass fiber reinforced plastic pressure vessel lining materials, characterized in that: include: S1: manufacturing a steel mold, wherein the steel mold is composed of a cylinder and a single head; S2: A layer of mold release film is attached to the inner surface of the steel mold, and the fiberglass pressure vessel lining material is layered on the inner surface of the steel mold according to the actual layering order and solidified into a shape. After demolding, the mold release film is removed to obtain multiple samples; S3: Add chemical medium into the sample, seal the opening with a sealing film, fix the sample, and start the experiment at the preset temperature; S4: taking out a sample from the multiple samples at a preset time interval, taking out the cylindrical sample with a single head, observing the appearance of the sample, measuring the mass, wall thickness and Barcol hardness of the sample and recording the formation parameter data, cutting out multiple annular samples at the contact point between the sample and the chemical medium, measuring the hoop tensile strength of the annular samples and taking an average value, and calculating the hoop tensile strength retention rate according to the parameter data and the average value of the hoop tensile strength; S5: Evaluate the chemical resistance of the FRP pressure vessel lining material. If the hoop tensile strength retention rate is higher, the chemical resistance of the FRP pressure vessel lining material is better; otherwise, the chemical resistance of the FRP pressure vessel lining material is worse. In S3, a chemical medium is added to the sample, the opening is sealed with a sealing film, a small hole is opened on the surface of the sealing film, the sample is placed vertically in a glass container and fixed securely, and then the experiment is started at a preset temperature.
2. The method for evaluating the chemical resistance of the lining material of a glass fiber reinforced plastic pressure vessel according to claim 1, characterized in that: In S1, the outer diameter of the cylinder is 100-300 mm, the thickness is 1-6 mm, and the length is 150-300 mm; The sealing head is elliptical, and its thickness is the same as that of the cylinder. A through hole with a diameter of 5-15 mm is opened at the center of the sealing head.
3. The method for evaluating the chemical resistance of the lining material of a glass fiber reinforced plastic pressure vessel according to claim 2, characterized in that: In S3, the sample is placed vertically, and the height of the chemical medium added therein is not less than 150 mm.
4. The method for evaluating the chemical resistance of the lining material of a glass fiber reinforced plastic pressure vessel according to claim 1, characterized in that: In S1, after the steel mold is manufactured, its surface and joints are polished.
5. The method for evaluating the chemical resistance of the lining material of a glass fiber reinforced plastic pressure vessel according to claim 1, characterized in that: In S2, the release film is a polyethylene film.
6. The method for evaluating the chemical resistance of the lining material of a glass fiber reinforced plastic pressure vessel according to claim 1, characterized in that: In S2, the ply thickness is 2-5 mm.
7. The method for evaluating the chemical resistance of the lining material of a glass fiber reinforced plastic pressure vessel according to claim 1, characterized in that: In S2, the lining material of the FRP pressure vessel is composed of impregnated glass fiber surface felt, chopped strand felt and glass cloth; the sample is cylindrical with a single head.
8. The method for evaluating the chemical resistance of the lining material of a glass fiber reinforced plastic pressure vessel according to claim 1, characterized in that: In S3, the sealing film is a polytetrafluoroethylene film.
9. The method for evaluating the chemical resistance of the lining material of a glass fiber reinforced plastic pressure vessel according to claim 1, characterized in that: In S4, five annular specimens with a width of 10-20 mm are cut at the contact point between the specimen and the chemical medium.
Citation Information
Patent Citations
Test method for evaluating corrosion resistance of coating
CN104266958A
High-strength glass fiber-reinforced plastic pipeline and production method thereof
CN104405962A